Endothelial progenitor cells: identity defined? - Timmermans, Frank; Plum, Jean; Yöder, Mervin C.; Ingram, David A.; Vandekerckhove, Bart; Case, Jamie (Journal of cellular and molecular medicine, 2009)
• Introduction • The proof‐of‐concept in vivo: the cell, the read‐out and the animal model ‐ The CEPC: Still a putative cell ‐ Do CEPCs play an essential role in vascular (patho)physiology? ‐ The in vivo read‐out and animal model • EPCs defined in vitro: the achilles heel in EPC biology ‐ EOCs and EC‐like cells ‐ What are potential caveats with in vitro defined cells? ‐ The search for the EOC precursor: lessons from embryonic development ‐ Do EOCs derive from an immature CEPC? ‐ Do EOCs derive from high proliferative vessel wall ECs? ‐ CEPCs and CECs: Different cells having the same identity? • Summary In the past decade, researchers have gained important insights on the role of bone marrow (BM)‐derived cells in adult neovascularization. A subset of BM‐derived cells, called endothelial progenitor cells (EPCs), has been of particular interest, as these cells were suggested to home to sites of neovascularization and neoendothelialization and differentiate into endothelial cells (ECs) in situ, a process referred to as postnatal vasculogenesis. Therefore, EPCs were proposed as a potential regenerative tool for treating human vascular disease and a possible target to restrict vessel growth in tumour pathology. However, conflicting results have been reported in the field, and the identification, characterization, and exact role of EPCs in vascular biology is still a subject of much discussion. The focus of this review is on the controversial issues in the field of EPCs which are related to the lack of a unique EPC marker, identification challenges related to the paucity of EPCs in the circulation, and the important phenotypical and functional overlap between EPCs, haematopoietic cells and mature ECs. We also discuss our recent findings on the origin of endothelial outgrowth cells (EOCs), showing that this in vitro defined EC population does not originate from circulating CD133+ cells or CD45+ haematopoietic cells.